Better Safe than Sorry? The Effects of Income Risk, Unemployment Risk and the Interaction of these Risks on Wages - Wolfgang Nagl (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2012)
We examine whether income and unemployment risks are compensated by individual wages. Using a portfolio approach we show that the marginal income risk effect on wages is always positive whereas the marginal unemployment risk effect crucially depends on the income risk. The interaction effect between both risk measures is negative. Using administrative panel data from Germany we confirm the theoretically predicted signs for both risks and their interaction effect.
Keywords: J30; J31; J64; 330; Income risk; unemployment risk; interaction effect; wages